A combined acoustic and dynamic model of a defective ball bearing. (9th June 2021) - Liu, Jing; Xu, Yajun; Pan, Guang
Highlights: An improved dynamic model of ACBB considering various friction torques and ball motion state is proposed. The previous acoustic emission model is extended to describe more degrees of freedom of ACBB. Effects of speed, load, and defect sizes on the acoustic characteristics for ACBB are investigated. Comparison results between the proposed and reported models depict the superiority of established approach. Abstract: Due to their special characteristics, angular contact ball bearings (ACBBs) are broadly applied in various mechancial systems. The working performance of rotating machinery can be determined by the internal ACBBs. Vibration and acoustic characteristics of ACCBs in various rotating machinery are becoming increasingly significant for the high-performance mechanical systems. An in-depth recognition of acoustic characteristics of ACBB can be helpful for condition monitoring of rotating machinery. This study proposes an improved dynamic model of ACBB to consider the influences of elastic hysteresis, differential sliding friction torques, and elastohydrodynamic lubrication (EHL) rolling on the ball motion state. A modified time-dependent excitation (TDE) model is developed for describing different kinds of defects in the outer ring of ACBB. The acoustic emission models given by Sharma [8] and Patil [9] are extended to describe more degrees of freedom of ACBB. Effects of speed, load, and defect sizes on the acoustic characteristics for ACBB are investigated. Comparison results between the proposed and reported models depict the superiority of established approach here. Note that the load, speed, and defect can greatly affect the acoustic characteristics of ACBB. The results improved that this model has ability to obtain the accurate acoustic characteristics of a defective ACBB.